The Derogatory Force and the Offensiveness of Slurs - Chang Liu (Institute of Philosophy of the Slovak Academy of Sciences, 2021)
Slurs are both derogatory and offensive, and they are said to exhibit “derogatory force” and “offensiveness.” Almost all theories of slurs, except the truth-conditional content theory and the invocational content theory, conflate these two features and use “derogatory force” and “offensiveness” interchangeably. This paper defends and explains the distinction between slurs’ derogatory force and offensiveness by fulfilling three goals. First, it distinguishes between slurs’ being derogatory and their being offensive with four arguments. For instance, ‘Monday’, a slur in the Bostonian argot, is used to secretly derogate African Americans without causing offense. Second, this paper points out that many theories of slurs run into problems because they conflate derogatory force with offensiveness. For example, the prohibition theory’s account of offensiveness in terms of prohibitions struggles to explain why ‘Monday’ is derogatory when it is not a prohibited word in English. Third, this paper offers a new explanation of this distinction from the perspective of a speech act theory of slurs; derogatory force is different from offensiveness because they arise from two different kinds of speech acts that slurs are used to perform, i.e., the illocutionary act of derogation and the perlocutionary act of offending. This new explanation avoids the problems faced by other theories.